An assessment of surface water quality and heavy metals involving the radioactive elements in Sungai Tunggak and Sungai Balok, Gebeng, Kuantan, Pahang: comparison between year 2014 and 2015 - Ab Wahab, Siti Umi Kalthum; Shaibullah, Siti Hajar; Abu Samah, Mohd Armi; Mohd. Aris, Mohd Shukri (Research India Publications, 2016)
Water pollution caused by radioactive elements and heavy metals has become serious threats to the survival of aquatic organisms, human, and environment especially in Pahang. This alarming circumstance has inspired the study to measure water quality parameters, concentration of radioactive elements and heavy metals in the rivers within an industrial area. For achieving these objectives, collected data was done for Balok and Tunggak Rivers in dry seasons (April – June) in the year 2014 and 2015. Both data were compared and analyzed based on different locations at the selected rivers in Gebeng industrial area, Pahang. METHODS: The physical parameters such as temperature, specific conductivity, pH, turbidity, and dissolved oxygen (DO) were measured by using hydrolab. The water samples were then collected for tracing the radioactive elements and heavy metals by using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Malaysian Interim National Water Quality Standard (INWQS) was used as reference. RESULTS: Heavy metals and water quality parameters were all within the permissible limit except for turbidity and specific conductivity in both years 2014 and 2015. Besides, radioactive elements investigated in this study showed that the concentration of one of the investigated elements was thorium, exceeded the permissible limit at the upstream area which recorded 2.54ppb in year 2014 and 0.75ppb in 2015. CONCLUSIONS: The study outcomes showed the pollutants presence were reflected to some water quality parameters from upstream, middle stream and downstream for both years.